3
$\begingroup$

From software, I get

$$\int \frac{\cos ^2 x+\cos (\sin x)}{\sin x \sin (\sin x)+1} \, dx=-2 \tan ^{-1}\left(\cos \left(\frac{x}{2}-\frac{\sin x}{2}\right) \csc \left(\frac{x}{2}+\frac{\sin x}{2}\right)\right)$$

I tried $t=\sin x,x=\arcsin t$ and get $$\int \frac{1-t^2+\cos t}{\sqrt{1-t^2} (1+t \sin t)} \, dt$$ Then, I can't figure out how to do it.

$\endgroup$
1
  • $\begingroup$ Did you try taking the derivative of the function on the right? $\endgroup$ – LL 3.14 May 16 '20 at 4:44
6
$\begingroup$

Rewrite the denominator

\begin{align} \sin x \sin (\sin x)+1 = &\frac12[\cos(x-\sin x) - \cos(x+\sin x)]+1 \\ = &\frac12[1-\cos(x+\sin x)] + \frac12[1+\cos(x-\sin x)] \\ = & \sin^2t_+ + \cos^2t_- \end{align} where $t_\pm=\frac x2 \pm \frac{\sin x}2$. Also rewrite the numeritor

\begin{align} \cos ^2x+\cos (\sin x)= &\cos x\cos(t_+ + t_-) + \cos(t_+ - t_-) \\ = &(1+\cos x)\cos t_+ \cos t_- + (1-\cos x)\sin t_+ \sin t_- \\ = & 2 \cos t_- \frac{d\sin t_+}{dx} - 2\sin t_+ \frac{d\cos t_-}{dx} \end{align}

Substitute above into the integrand to obtain

\begin{align} \int \frac{\cos ^2 x+\cos (\sin x)}{\sin x \sin (\sin x)+1} \, dx & =\int \frac {2 \cos t_- \frac{d\sin t_+}{dx} - 2\sin t_+ \frac{d\cos t_-}{dx} }{ \sin^2t_+ + \cos^2t_-} \\ & =-2\int \frac {\sin^2 t_+ \frac{d}{dx}\left(\frac{\cos t_-}{\sin t_+}\right) }{ \sin^2t_+ + \cos^2t_-} \\ & =-2\int \frac {\frac{d}{dx}\left(\frac{\cos t_-}{\sin t_+}\right) }{ 1 + \left(\frac{\cos t_-}{\sin t_+}\right)^2} = -2\tan ^{-1}\left(\frac{\cos t_-}{\sin t_+}\right) +C \end{align}

$\endgroup$
0
$\begingroup$

Because

$$\begin{align} \left(\arcsin\frac{y+\sin y}{1+y\sin y}\right)'=\frac{1-y^2+\cos y}{(1+y\sin y)\sqrt{1-y^2}} \end{align}$$ Then let y=sinx, Problem solved.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.